Sustainability challenges of clean-energy critical minerals: copper and rare earths - O'Kelly, Brendan (My University, 2025)
The transition to a clean-energy economy in an effort to mitigate climate change has brought a need for intense mining exploration of a critical class of minerals, previously mined and used at a fraction of what is required today and for the upcoming decades. For some common metals, such as copper, major deficits are forecasted for 2030, and for some less common ones, such as rare earths, mined quantities have recently increased 32 times relative to those in the mid-1950s and are expected to increase sevenfold from current levels by 2040. This situation is expected to become more severe given the long time span needed for exploration of new sites, the declining ore grade of existing mines, the geographical distribution of these minerals and the environmental degradation caused by mining and mineral processing activities. It becomes, hence, critical to improve existing mining operations vastly, reduce waste volumes and fresh water use, reduce environmental impacts and recover increased quantities of minerals from mine tailings, as well as from the recycling of post-production products. This paper focuses on copper and rare earths to expound on their exploitation issues, their processes, the sustainable utilisation of mineral waste and tailings and their recovery from end-of-life consumer and industrial items. Keywords:
PUBLISHED
Keywords: clean-energy minerals, copper waste utilisation, end-of-life product recycling, mine tailings, rare earths, UN SDG 6: Clean water and sanitation, UN SDG 7: Affordable and clean energy, UN SDG 15: Life on land; International Development; Smart & Sustainable Planet; COPPER; Drilling and Mining; Environmental Geotechnics; Geotechnical Engineering; Geotechnics; MINE TAILINGS; MINE WASTE; MINING; Mining Engineering; RARE-EARTH ELEMENTS; REE; TAILINGS; Waste Management; rare-earths